2009
DOI: 10.1021/ic802052u
|View full text |Cite
|
Sign up to set email alerts
|

A New Dinuclear Ruthenium Complex as an Efficient Water Oxidation Catalyst

Abstract: A dinuclear ruthenium complex, which acts as a molecular catalyst for water oxidation, has been synthesized and characterized. The electronic and electrochemical properties were studied by UV-vis spectroscopy and cyclic voltammetry. The oxidation potentials of the complex are significantly lowered by introducing a negatively charged carboxylate ligand, in comparison with those of the reported complexes that have neutral ligands. The catalytic activity of the complex toward water oxidation using Ce(NH(4))(2)(NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 33 publications
1
105
1
1
Order By: Relevance
“…[4] While the first two topics have been the core of artificial photosynthesis for the last two decades, and also the subject of comprehensive reviews, [13][14][15][16][17][18][19][20][21][22][23] significant achievements have been made only in the recent years as far as the design of efficient molecular catalysts for both hydrogen and oxygen evolution is concerned. These comprise FeFe, [24] NiRu, [25][26][27][28][29][30] NiMn, [31] and NiFe [25,[32][33][34] models of the active sites of hydrogenases as well as manganese [35] and ruthenium [36][37][38][39][40] catalysts as functional mimics of the PSII OEC. These systems have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
“…[4] While the first two topics have been the core of artificial photosynthesis for the last two decades, and also the subject of comprehensive reviews, [13][14][15][16][17][18][19][20][21][22][23] significant achievements have been made only in the recent years as far as the design of efficient molecular catalysts for both hydrogen and oxygen evolution is concerned. These comprise FeFe, [24] NiRu, [25][26][27][28][29][30] NiMn, [31] and NiFe [25,[32][33][34] models of the active sites of hydrogenases as well as manganese [35] and ruthenium [36][37][38][39][40] catalysts as functional mimics of the PSII OEC. These systems have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
“…[14,36] Negatively charged ligands can lower the oxidation potentials of metal complexes and thus stabilise the high oxidation states of the metal ions, [37] and so we have employed carboxylate ligands to synthesise highly efficient water oxidation catalysts. We have previously reported dinuclear (D and E, Figure 1) [20][21][22] and mononuclear ruthenium complexes, [18,19,23] which indeed promise high activities. In addition to manganese-and ruthenium-based complexes, in 2008 Bernhard and co-workers reported iridium-based aquo complexes that can also catalyse homogeneous water oxidation in the presence of CeA C H T U N G T R E N N U N G (NH 4 ) 2 A C H T U N G T R E N N U N G (NO 3 ) 6 (Ce IV ) as oxidant with turnover numbers (TONs) of over 2000.…”
Section: Introductionmentioning
confidence: 83%
“…44 The bpc 2− symmetric ligand coordinates to Ru in an unsymmetrical manner, generating an organometallic dinuclear Ru complex with one of the C-atoms of the pyridazine group bonded to the Ru center as shown in Figure 7(b). It is reported that addition of Ce IV to this complex generates molecular oxygen with a TN of 1700 and an efficiency of 16.3% compared to the oxidant together with a catalytic amount of CO 2 , whose origin is not known.…”
Section: Pyridazine-bridged Dinuclear Ru Complexesmentioning
confidence: 99%